2018
DOI: 10.1176/appi.ajp.2017.17040469
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Developmental Trajectories in Adolescents After Initiating Drinking

Abstract: Initiation of drinking during adolescence, with or without marijuana co-use, disordered normal brain growth trajectories. Factors possibly contributing to abnormal cortical volume trajectories include peak consumption in the past year and family history of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 33 publications
11
142
1
1
Order By: Relevance
“…The drinking threshold was based on National Institute on Alcohol Abuse and Alcoholism guidelines for risky drinking that varied by age and sex. As stated previously (Pfefferbaum et al, ), the maximum drinking days was five for those 12–15.9 years old, 11 for those 16–16.9 years old, 23 for those 17–17.9 years old, and 51 for those age 18 and older. The maximum allowable drinks per occasion was three for female participants at any age but varied by age for male participants, for whom the maximum drinks per occasion was three for those 12–13.9 years old, four for those 14–19.9 years old, and five for those age 20 and older.…”
Section: Methodssupporting
confidence: 69%
“…The drinking threshold was based on National Institute on Alcohol Abuse and Alcoholism guidelines for risky drinking that varied by age and sex. As stated previously (Pfefferbaum et al, ), the maximum drinking days was five for those 12–15.9 years old, 11 for those 16–16.9 years old, 23 for those 17–17.9 years old, and 51 for those age 18 and older. The maximum allowable drinks per occasion was three for female participants at any age but varied by age for male participants, for whom the maximum drinks per occasion was three for those 12–13.9 years old, four for those 14–19.9 years old, and five for those age 20 and older.…”
Section: Methodssupporting
confidence: 69%
“…Clearly, change toward normal levels of brain tissue volumes (Durazzo et al, 2015) and white matter integrity (Pfefferbaum et al, 2014) together with improvement in neuropsychological functioning beyond simple practice effects (Durazzo and Meyerhoff, 2020;Sullivan et al, 2000) has been observed with quantitative, longitudinal assessment and provides evidence for a role for changes in drinking levels to be causative. Conversely, prospective studies of adolescents before and after initiating appreciable alcohol drinking reported accelerated gray matter volume loss predominantly in frontal cortex compared with adolescents who remained no-to-low drinkers (Pfefferbaum et al, 2018a). What the actual biological mechanisms of change are remain to be discovered and may rely on animal models (e.g., Zahr et al, 2013).…”
Section: Frontal System Insult and Recoverymentioning
confidence: 99%
“…Volume measures, provided by the competition organizers, were derived from the T1-weighted images as follows: the Minimal Processing pipeline [8] transformed the raw data into NIfTI format. Afterwards, the NCANDA pipeline [16] defined a brain mask by non-linearly mapping the SRI24 atlas [17] to the T1-weighted images, and it removed noise and corrected for bias-field inhomogeneities. Several skull-stripping methods were used with bias-field corrected and non-bias-field corrected images, and a majority voting of the resulting masks refined the brain masks from the previous step.…”
Section: Image Pre-processingmentioning
confidence: 99%